A case of pulmonary vein thrombosis with transient ischemic attacks diagnosed by contrast‐enhanced computed tomography - Yoshimasa Ogata; Keisuke Aita; Juri Maeda; Risa Shiragami; Masaaki Hagiya; Kiyohiko Shuto; Fumitaka Nakamura; Masao Yamaguchi (Respirology Case Reports)
Abstract Pulmonary vein thrombosis (PVT) is rarer than pulmonary artery thrombosis (PAT). PVT is potentially fatal but is often overlooked due to its nonspecific symptoms. We present a case with PVT accompanied by paroxysmal atrial fibrillation. The symptoms were limited to transient ischemic attacks. Contrast‐enhanced computed tomography (CT), which showed a thrombus in the right pulmonary vein trunk, was useful in diagnosing PVT. After switching the patient's anticoagulant from dabigatran etexilate to apixaban, the thrombus disappeared within 5 months. Contrast‐enhanced CT is a useful and common tool for diagnosis and follow‐up of PVT.